Family-based risk factors for non-suicidal self-injury: Considering influences of maltreatment, adverse family-life experiences, and parent–child relational risk. (June 2016) - Martin, Jodi; Bureau, Jean-François; Yurkowski, Kim; Fournier, Tania Renaud; Lafontaine, Marie-France; Cloutier, Paula
Abstract: The current investigation addressed the potential for unique influences of perceived childhood maltreatment, adverse family-life events, and parent-child relational trauma on the lifetime occurrence and addictive features of non-suicidal self-injury (NSSI). Participants included 957 undergraduate students (747 females; M  = 20.14 years, SD  = 3.88) who completed online questionnaires regarding the key variables under study. Although self-injuring youth reported more experiences with each family-based risk factor, different patterns of association were found when lifetime engagement in NSSI or its addictive features were under study. Perceived parent-child relational trauma was uniquely linked with NSSI behavior after accounting for perceived childhood maltreatment; adverse family-life events had an additional unique association. In contrast, perceived paternal maltreatment was uniquely related with NSSI's addictive features. Findings underline the importance of studying inter-related family-based risk factors of NSSI simultaneously for a comprehensive understanding of familial correlates of NSSI behavior and its underlying features.